Identifying and Ranking Key Competencies of Managers for Realization of Human Resources Excellence at Home Appliances Manufacturing Companies - Mir Hadi Moazen Jamshidi (مطالعات منابع انسانی, 2019)
Background and Objective: A prerequisite for the implementation of human resources excellence plans is that managers have the necessary competencies. This study aimed to identify the key competencies of managers for the excellence of human resources. Methodology: In this study, a sequential mixed method (qualitative-quantitative) research design was implemented in three steps. The grounded theory (GT) was employed in the first step to identify managerial competencies by interviewing 18 managers of 8 home appliances manufacturing companies in Iran. The Delphi method was then used in the second step to determine the importance of each competency. After that, the partial least squares structural equation modeling (PLS-SEM) technique was employed to evaluate the effects of these competencies on the results of human resources excellence in the third step where 114 intra-organizational departments and their managers (114 individuals) were monitored through the complete enumeration method. Findings: Regarding the effectiveness of establishment of a human resources excellence system, 16 key competencies were identified for managers in five areas of individual, communicational-social, management and leadership, strategic, and complementary competencies. Conclusion: Enabling managers to benefit more from these key competencies can help facilitate the progress of human resources excellence plans in organizations.